2012
DOI: 10.1002/chem.201202100
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereo‐ and Regioselective Hydrostannylation of Internal Alkynes Promoted by Simple Boric Acid in Air

Abstract: Facile hydrostannylation of alkynes in air: The ability to prepare vinylstannanes of high regio- and sterochemical fidelity in a safe manner employing a simple operational set up, especially on a large scale, has remained elusive. This study has shown that all of the autoxidation products of Et(3) B and boronic acids are capable of promoting hydrostannylation. Most importantly, simple boric acid itself can also promote the hydrostannylation of highly functionalized internal alkynes with complete selectivity un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Recently, Organ and co‐workers found that regio‐ and Z ‐selective hydrostannation of propargylic alcohol derivatives with tributyltin hydride (Bu 3 SnH) is possible by extending the reaction time at room temperature or heating at 80 °C with BEt 3 plus air system 6e. In the consecutive paper, they reported that borinates, boronates, and even boric acid in air can also promote the hydrostannation with a mechanism involving ionic species 6f. Diethylzinc has been used as a radical initiator for tin‐mediated radical reactions at low reaction temperature, [7 g] but its strong nucleophilicity is a potential drawback 6b.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Organ and co‐workers found that regio‐ and Z ‐selective hydrostannation of propargylic alcohol derivatives with tributyltin hydride (Bu 3 SnH) is possible by extending the reaction time at room temperature or heating at 80 °C with BEt 3 plus air system 6e. In the consecutive paper, they reported that borinates, boronates, and even boric acid in air can also promote the hydrostannation with a mechanism involving ionic species 6f. Diethylzinc has been used as a radical initiator for tin‐mediated radical reactions at low reaction temperature, [7 g] but its strong nucleophilicity is a potential drawback 6b.…”
Section: Methodsmentioning
confidence: 99%
“…We mention this here specifically because our 2005 experimental results strongly controvert the recent mechanistic proposal of Organ and coworkers shown in Scheme ,,, who, without any genuinely supportive experimental evidence, advanced the claim that the initially formed α‐trialkyl‐ and α‐triaryl‐stannyl‐β‐alkyl‐vinyl radicals in O‐directed free radical hydrostannation reactions subsequently engage in a single electron transfer (SET) process with triplet O 2 , to generate an α‐stannylvinyl cation and superoxide anion. Such α‐stannylvinyl cations are then suggested to undergo ionic reduction with the excess stannane that is present in the solution to give the observed vinylstannane α‐addition products and a trialkyl‐ or triaryl‐stannyl cation, which itself is reduced by a second reverse single electron transfer (SET) from the liberated superoxide ion, to fashion a new tin radical which further propagates the radical chain.…”
Section: Our 2005 Experimental Investigations Into the Mechanism Of Tmentioning
confidence: 80%
“…If we now revisit the issue of product distribution in the free radical hydrostannation of 293 under conditions of low stannane concentration (Scheme ), the very fact that the 5‐exo‐trig cyclisation product 298 was the only cyclisation product that was observed in this study very strongly indicates that our O‐directed hydrostannation process with Ph 3 SnH/cat. Et 3 B/O 2 must be totally free radical in its nature and that it cannot have any cationic component to it whatsoever, which is in total conflict with what was proposed later by Organ et al,,, in 2013 (Scheme ).…”
Section: Our 2005 Experimental Investigations Into the Mechanism Of Tmentioning
confidence: 87%
See 2 more Smart Citations